CD8+ T cells mediate the impact of gut dysbiosis and short-chain fatty acid deficiency on accelerated arthritis progression in collagen-induced arthritis mice - Zhao, Xiangcong; Song, Yuhang; Zhao, Wenpeng; Shang, Lili; Fan, Chunxue; Xie, Jianfang (Frontiers in Immunology, 2025)
ObjectiveThis study aims to investigate the association between gut microbiota dysbiosis and phenotypic alterations in immune cells across multiple tissues in a collagen-induced arthritis (CIA) mouse model, and to elucidate the bidirectional regulatory mechanisms underlying the interaction between the gut microbiota and host immune responses.MethodsTwelve 6-8-week-old male DBA/1 mice were randomly assigned to either a collagen-induced arthritis (CIA) model group (n=6) or a normal (NOR) group (n=6). At the end of the experiment, feces, peripheral blood (PB), spleen (SP), intestinal segments, joint tissues and serum were collected. We employed an integrated analytical approach comprising fecal 16S ribosomal DNA gene sequencing, short-chain fatty acid (SCFA) metabolomics, flow cytometric detection of IgA-coated bacteria, immune phenotyping by flow cytometry, and cross-group network analysis to systematically evaluate gut microbial composition and host cellular immune profiles.ResultsCIA mice developed polyarthritis, accompanied by a decrease in splenic T and NK cells and an increase in B cells. CD8+ T cells were significantly increased in mesenteric lymph nodes (MLN) and intestinal mucosa (IM). The gut microbiota exhibited reduced α-diversity, enriched Bacteroidetes, depleted Firmicutes, and decreased Lachnospiraceae_NK4A136_group. Fecal SCFA levels declined, while the proportion of IgA-coated bacteria increased. Functional prediction analysis indicated downregulation of microbial gene pathways associated with xylan decomposition, amino acid metabolism, and drug efflux, whereas pathways related to cell wall synthesis were upregulated. Cross-omics analysis confirmed significant correlations between these immune cells and specific bacterial genera.ConclusionThe reduction of SCFAs synthesis caused by gut microbiota dysregulation in CIA mice is related to the expansion of intestinal CD8+ T cells and may further promote the imbalance of T/B cells in the spleen; this gut microbiota -SCFA- CD8+ T cell axis may be involved in the occurrence and development of arthritis.